Influência do perfil de velocidade do escoamento sobre a medição ultrassônica de vazão por tempo de trânsito - Mathias, Rogério Bolzan (2010)
This study aims to examine the influence of velocity profile measurement by ultrasonic transit time flow. First of all, it is performed an approach technique, with the modeling problem, and it is analyzed the measurement uncertainty as well. Next, an acoustic wave in mobile environment is studied in relation to the influence of velocity profile on transit times, sound wave drag and, consequently, the flow calculation. The results were obtained considering uniform velocities and a Hinze profile, through numerical simulation. Finally, this same behavior was studied for a non-uniform velocity profile.